Estimating wage equations for Hungarian higher-education graduates - Peter Galasi (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2003)
The paper investigates the wage determination of Hungarian highereducation graduates with using two samples of Hungarian careerbeginners, applying IV techniques and the multiple indicator solution so as to diminish potential estimation biases due to endogeneity of independent variables (especially the education variable) and the simultaneity of wages and working time. The results show that university education yields considerable wage premium as compared to college education, and that the return to education would be significantly underestimated by ols. The estimates confirm that foreign-language and IT knowledge also produce advantages in terms of wages.
Keywords: 330